Internet Use, Online Communication, and Ties in Americans’ Networks - Chen, Wenhong (Social science computer review, 2013)
Drawing on nationally representative survey data, this article examines the implications of Internet use and online communication for strong and weak ties in Americans’ social networks. In line with the existing literature, this research shows that frequent Internet use and online communication are associated with a larger core discussion network and a more extensive position-generated network. More importantly, this research provides a finer tuned analysis by disaggregating the overall network into strong and weak ties. First, Internet use—but not online communication—is positively related to weak-tie based network extensity in the position-generated networks. Second, Internet use and online communication are positively related to the number and the proportion of strong ties in Americans' core discussion networks. These results help reconcile some of the conflicting findings and interpretations based on different network measures in the exiting literature.